COPING STRATEGY MODEL OF CYBERBULLY VICTIMS AMONG UNIVERSITY STUDENTS - Mohammad Aminul Haq Mohd Ghazali (Tesis, 2022)
The objectives of this thesis are (1) to identify the appropriate coping strategy for cyberbully-victims ; (2) to propose an effective coping strategy model for cyberbully-victim; and (3) to access the students' knowledge on technological prevention action in coping with cyberbullying